Current Reference Framework for Diagnosis Pedagogical - Narciso García Nieto (Tendencias Pedagógicas, 2015)
The present work, it has as purpose plan a conceptual frame of the current diagnosis in the educational area or pedagogic diagnosis, taking as a reference the analysis of its past, its present and its projection towards the future. It will split for it, of the justification motivated of the diagnostic activity linked fundamentally, to the educational individualization, on the support and pupils’ treatment with educational special needs (functional diversity) and to the modification and/or cognitive improvement, as basic and referential element of an educational specializing and diversified intervention. Chord with the circumstances and educational needs asked nowadays, the following ones propose as prior nuclei of activity for the diagnosis: The emotional intelligence, the competition curricular, the diagnosis in the transitions, as challenges and social and educational current demands. They are included besides, some considerations it brings over of the investigation and methodological innovation on the current diagnosis, which seem to offer and to guarantee improvements of future for this discipline and its professional practice. The work finishes formulating some conclusive reflections.